Relevansi Teori Oplossing dalam Penanganan Sengketa Terkait Keputusan Pengadaan Barang dan Jasa Pemerintah - Paulus Rudy Calvin Sinaga; Anna Erliyana (The Constitutional Court of the Republic of Indonesia, 2022)
The Indonesian State Administrative Court has applied the oplossing theory, where claims related to disputes over the procurement of government goods or services are considered to be merged in the civil realm so that they are assumed to be not authorized to handle the dispute. This research is normative juridical research by comparing the practice of handling cases of government procurement of goods and services in the Indonesian State Administrative Court, the Constitutional Court, and the French Administrative Court. Research shows that there are inconsistencies in the Indonesian state administrative court regarding the interpretation of the oplossing theory after the enactment of Law Number 30 of 2014 concerning Government Administration, while in France, the plaintiff can file a lawsuit in the form of annulment of administrative decisions related to the procurement of government goods and services or a compensation claim. The implication of eliminating the oplossing theory is that a third party can file a claim for compensation against a dispute over the procurement of government goods and services in the state administrative court in accordance with the Constitutional Court Decision Number 22/PUU-XVI/2018 regarding the grace period for filing a lawsuit by a third party.